Poder soberano e biopolítica no combate às drogas no Brasil - Sanches, Raphael Rodrigues [UNESP]; Rocha, Luiz Carlos da [UNESP] (My University, 2011)
In the last two or three decades has become common the debate on the harmful effects produced by trade and use of illicit substances in Brazil. The "drug problem" as it became known worldwide in official and media discourses, has become, if not the only, at least the most important determinant of a series of social ills that affect both the rich countries (classified as consumers), and the poor countries (the producers and exporters of these "evil substances"). This situation that today is extremely pernicious, may be better understood through some elements of the story of its constitution. In this sense, we draw a succinct history of drug prohibition worldwide and we use the Foucauldian concept of biopower and the concept of “death policy” designed by André Saldanha Costa to comment briefly on the "drug problem" in Brazil. In this initial approach, we can affirm the importance of these two concepts for the understanding of the “depoliticized life" of drug traffickers as well as the governmental policies, both legal and health focused on this issue.

Nas duas ou três últimas décadas tornou-se comum o debate em torno dos malefícios produzidos pelo comércio e uso de substâncias ilícitas no Brasil. O “problema das drogas”, como ficou mundialmente conhecido nos discursos oficiais e midiáticos, passou a ser, se não o único, ao menos o mais importante determinante de uma série de mazelas sociais que atingem tanto os países ricos (classificados de consumidores), quanto os países pobres (os produtores e exportadores das “diabólicas substâncias”). Essa situação que, nos dias de hoje, afigura-se como extremamente perniciosa pode ser melhor entendida resgatando-se alguns elementos da história de sua constituição. Nesse sentido, traçamos uma suscinta história da proibição das drogas em âmbito mundial e nos valemos do conceito foucaultiano de biopoder e o de tanatopolítica da “Guerra às Drogas” desenvolvido por André Saldanha Costa para tecer breves comentários sobre o “problema das drogas” no Brasil. Nessa primeira aproximação, podemos afirmar a importância desses dois conceitos para o entendimento da “vida despolitizada” dos traficantes de drogas, bem como das políticas governamentais, tanto jurídicas quanto da saúde, voltadas a essa questão.
Sovereign power and biopolitics in the fight against drugs in Brazil
Keywords: Biopolitics; Illict drugs; War on drugs; Biopolítica; Drogas ilícitas; Guerra às drogas